Designing an Adaptive Instructional Architecture for Islamic Education: A Theoretical Approach to Cognitive Personalization - Ahmad Silmul Fuady; Suci Silmiyah; Reza Aulia Agustin; Nurul Shofiah Al Bahri; Nurul Syarifatul Bahri (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The growing recognition of cognitive diversity in contemporary education has exposed the inadequacy of rigid instructional media within Islamic learning environments, where standardized delivery often fails to accommodate variations in learners’ comprehension patterns, reflective capacities, and digital literacy competencies. Responding to this challenge, this study conceptualizes an adaptive instructional architecture designed to personalize Islamic educational experiences through cognitively responsive learning pathways. Utilizing a conceptual design framework, the study synthesizes Cognitive Load Theory, adaptive learning principles, and classical Islamic pedagogical traditions to construct a theoretically grounded model capable of aligning instructional delivery with individual learner profiles. The analysis yields a three-layered architecture comprising a Diagnostic Layer for identifying cognitive characteristics, a Logic Layer for determining adaptive instructional decisions, and a Content Adaptation Layer for dynamically restructuring learning materials according to learner needs and epistemological contexts. The architecture facilitates more meaningful engagement with Islamic knowledge by reducing cognitive friction while strengthening reflective learning and ethical reasoning. Ultimately, this blueprint suggests a paradigm shift in Islamic educational technology by positioning AI-driven personalization as a form of digital Ijtihad capable of transforming student-media interaction into a more adaptive, reflective, and intellectually resonant educational process.